Nightrise / 3. - Horowitz, Anthony, 1955- (Gatekeepers, 2007)
After telepathic twins Jamie and Scott are attacked by the evil Nightrise Corporation, one of them is imprisoned while the other escapes, left to fight with the other three gatekeepers against the evil Old Ones in order to save his sibling and prevent the destruction of humanity.